1997
DOI: 10.1046/j.1365-2648.1997.1997026408.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting autonomy and independence for older people within nursing practice: a literature review

Abstract: The principles of promoting autonomy and independence underpin many approaches to improving the quality of nursing care for older people in whatever setting, and are in line with wider developments in health care such as the Patient's Charter. However, these concepts require careful definition if nursing practices which might promote autonomy and independence are to be identified. Although the generalizability of the research-based literature in this field is limited by a focus upon older people in continuing-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 52 publications
4
98
0
5
Order By: Relevance
“…It may improve satisfaction with care in hospital settings (Suhonen, Valimaki, & Leino-Kilpi, 2005) and promote greater autonomy and independence for older people who need care (Davies, Laker, & Ellis, 1997;Flesner & Rantz, 2004). In long-term care settings, individualization has been used to improve the quality of care for individuals with severe dementia (Allen-Burge, Stevens, & Burgio, 1999;Hallberg & Norberg, 1993;Morgan & Stewart, 1997) and for individuals who need end-of-life care (Heyland et al, 2006).…”
Section: Individualized Care: Process and Outcomesmentioning
confidence: 99%
“…It may improve satisfaction with care in hospital settings (Suhonen, Valimaki, & Leino-Kilpi, 2005) and promote greater autonomy and independence for older people who need care (Davies, Laker, & Ellis, 1997;Flesner & Rantz, 2004). In long-term care settings, individualization has been used to improve the quality of care for individuals with severe dementia (Allen-Burge, Stevens, & Burgio, 1999;Hallberg & Norberg, 1993;Morgan & Stewart, 1997) and for individuals who need end-of-life care (Heyland et al, 2006).…”
Section: Individualized Care: Process and Outcomesmentioning
confidence: 99%
“…11,18,21,22 Other studies have focused on factors closely related to management style and organizational climate. [23][24][25][26][27][28][29][30] Typical of these studies is Schaefer and Moos' 29 investigation of the effect of work stressors and work climate on job morale and functioning of staff in continuing-care settings for older people. They found that both specific work stressors and overall work climate have a significant impact on job morale and functioning.…”
Section: Contextual Factorsmentioning
confidence: 99%
“…Self-care equipment is typically said to empower care recipients, promote their autonomy and independence (Ellenbecker et al, 2008) -central concepts/aims within medicine and health care (Russel, 2007). In particular, measures to improve the quality of nursing care for elderly people are often motivated by independence (Davies et al, 1997). In-need persons are generally assumed to prefer self-care over traditional institutionalized care (Kenner, 2008).…”
Section: Self-carementioning
confidence: 99%